Menjembatani Antara Norma Agama dan Realitas Sosial (Studi Kasus tentang Dampak Sosial Kehamilan Diluar Nikah pada Individu Muslim di Banjarsari, Surakarta pada Masa Covid 19) - Suratno, Suratno (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
During the pandemic, early marriage due to pregnancy out of wedlock increased in various parts of Indonesia, as well as in the Banjarsari sub-district. Pregnancy outside of marriage certainly has a social impact on society. The reality in society in dealing with social impacts is sometimes contrary to religious norms. This study discusses how to compromise between social reality and religious norms in dealing with the social impacts of pregnancy outside of marriage. By using qualitative methods and field research, the researcher uncovered several contradictory social realities in society, among others related to family and environmental disgrace, the marriage of pregnant women, child lineage, inheritance, and guardianship of daughters due to adultery. There is a meeting point between social reality and religious norms related to attitudes towards the social impact of pregnancy outside of marriage because Islamic law is guaranteed to be by all places and times.